What’s in a Name?: Exploring the Implications of Eurocentric (Re)naming Practices of Aboriginal and Torres Strait Islander Nomenclature in Australian Education Practices - Weuffen, Sara; Cahir, Fred; Zeegers, Margaret (The Australian Journal of Indigenous Education, 2016)
The aim of this article is to provide teachers with knowledge of ways in which Eurocentric (re)naming practices inform contemporary pedagogical approaches, while providing understandings pertinent to the mandatory inclusion of the cross-curriculum priority area: Aboriginal and Torres Strait Islander histories and cultures (Australian Curriculum Assessment and Reporting Authority, 2015). While we have focused on Eurocentric naming practices, we have also been conscious of names used by Aboriginal peoples and Torres Strait Islanders to name themselves and others and as non-Indigenous Australians we acknowledge that it is not our place to explore these in detail, or offer alternatives. In this article, we have explored the history of nomenclature as it relates to original inhabitants, the connotations of contemporary (re)naming practices in Australian education and discussed the importance of drawing on cultural protocols and engaging local communities for teaching and learning of Aboriginal and Torres Strait Islander histories and cultures. It is anticipated that discussions arising from this article may open up spaces where teachers may think about ways in which they approach Aboriginal and Torres Strait Islander histories and cultures.